Impact of Digital Technology on Entrepreneurship in Fashion Departement if Vocational High School - Afri Ola Dewi; Muhammad Giatman; Yuliana (Enrichment : Journal of Management, 2022)
This study aims to determine how the application of entrepreneurship in the field of fashion at SMKN 1 Ampek Angkek. This study uses a descriptive qualitative approach. The research instrument in the form of a questionnaire filled out by students was then analyzed to see the proportion of student interest and the form of entrepreneurship they have in using social media platforms. The results showed that 95% of students carried out entrepreneurial activities using social media, especially Tik Tok. They take advantage of information technology in the form of easy internet access with their social media account platforms in entrepreneurship to introduce their work.